PMT DARK CURRENT REDUCTION USING THERMOELECTRIC COOLING UNIT TE-206TSRF - Abood, Kamal M (Al-Nahrain Journal of Science, 2010)
Photomultiplier Tube (PMT) type EMI 9863Q with its housing and power supply of rang (1.5-3) kV,beside of the cooling unit type TE-206TSRF are used to perform this research. The evaluation of PMT darkcurrent pulses count are carried out in laboratory at different high voltage and at different temperatures ,theresults of these test, are plotted as a testing curves for this type of PMT. The research includes two tests ,onefor perform the affect of cooling on the dark pluses counts, and the second test for determined time intervalsfor PMT housing can be kept the cooling . The maximum dark pluses count at 0 C Temp is 18000, where at-10 C is 4000, and at -20 C is 1000 at same H.V (2.5 kV).The PMT housing cooling stage times are sec for-10, sec for -20, sec for -30.